Homology Requirements for Efficient, Footprintless Gene Editing at the CFTR Locus in Human iPSCs with Helper-dependent Adenoviral Vectors - Donna J Palmer; Nathan C Grove; Jordan Ing; Ana M Crane; Koen Venken; Brian R Davis; Philip Ng (Elsevier, 2016)
Helper-dependent adenoviral vectors mediate high efficiency gene editing in induced pluripotent stem cells without needing a designer nuclease thereby avoiding off-target cleavage. Because of their large cloning capacity of 37 kb, helper-dependent adenoviral vectors with long homology arms are used for gene editing. However, this makes vector construction and recombinant analysis difficult. Conversely, insufficient homology may compromise targeting efficiency. Thus, we investigated the effect of homology length on helper-dependent adenoviral vector targeting efficiency at the cystic fibrosis transmembrane conductance regulator locus in induced pluripotent stem cells and found a positive correlation. With 23.8 and 21.4 kb of homology, the frequencies of targeted recombinants were 50-64.6% after positive selection for vector integration, and 97.4-100% after negative selection against random integrations. With 14.8 kb, the frequencies were 26.9-57.1% after positive selection and 87.5-100% after negative selection. With 9.6 kb, the frequencies were 21.4 and 75% after positive and negative selection, respectively. With only 5.6 kb, the frequencies were 5.6-16.7% after positive selection and 50% after negative selection, but these were more than high enough for efficient identification and isolation of targeted clones. Furthermore, we demonstrate helper-dependent adenoviral vector-mediated footprintless correction of cystic fibrosis transmembrane conductance regulator mutations through piggyBac excision of the selectable marker. However, low frequencies (≤ 1 × 10−3) necessitated negative selection for piggyBac-excision product isolation.